1995
DOI: 10.1126/science.7542803
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of an IgE-Dependent Histamine-Releasing Factor

Abstract: An immunoglobulin E (IgE)-dependent histamine-releasing factor (HRF) produced by lymphocytes of atopic children and present in biological fluids of allergic patients has been identified and purified. Amino-terminal sequencing revealed extensive homology to a mouse protein, p21, and its human homolog, p23. Both recombinant proteins caused histamine release from the human basophils of a subpopulation of donors, and this release was dependent on IgE. Polyclonal antibodies recognized and removed the biological act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
246
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 353 publications
(252 citation statements)
references
References 23 publications
4
246
0
2
Order By: Relevance
“…The first report on a functional association of TCTP appeared in 1995. Susan MacDonald and co-workers (Baltimore) identified an extracellular function of this protein as 'histamine-releasing factor' (HRF) present in biological fluids of allergic patients (MacDonald et al 1995). This discovery led to a series of studies exploring the extracellular signalling function of HRF/TCTP in allergic and inflammatory responses, as recently reviewed by Dr.…”
Section: The 'Translationally Controlled Tumour Protein Tctp': Names mentioning
confidence: 99%
See 3 more Smart Citations
“…The first report on a functional association of TCTP appeared in 1995. Susan MacDonald and co-workers (Baltimore) identified an extracellular function of this protein as 'histamine-releasing factor' (HRF) present in biological fluids of allergic patients (MacDonald et al 1995). This discovery led to a series of studies exploring the extracellular signalling function of HRF/TCTP in allergic and inflammatory responses, as recently reviewed by Dr.…”
Section: The 'Translationally Controlled Tumour Protein Tctp': Names mentioning
confidence: 99%
“…In 1995, Susan Macdonald's group first described the presence of an 'IgE-dependent histamine-releasing factor (HRF)' in biological fluids of allergic patients, which was also produced by lymphocytes of atopic children (MacDonald et al 1995). The molecular characterisation revealed that this protein is identical to TCTP (or p21/p23).…”
Section: Tctp As Extracellular 'Signaling Molecule' In Immune Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…En outre, des concentrations plasmatiques élevées d'anticorps IgE, qui se lient aux basophiles et aux mastocytes et qui peuvent déclencher la libération d'histamine, ont été associées à la gravité de l'infection par Plasmodium falciparum [20]. Outre la libération d'histamine déclenchée par les IgE, le HRF (histamine-releasing factor), un peptide décrit chez l'homme et la souris, provoque la libération d'histamine, d'IL-4, et d'IL-13 par les basophiles [21]. Ce peptide appartient à une famille de protéines appelées protéines de tumeurs contrôlées au niveau traductionnel (TCTP).…”
Section: Relations Entre Histamine Et Infection Par Plasmodiumunclassified